PENERAPAN FREKUENSI PEMBERIAN POC JAKABA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SAWI HIJAU (Brassica Juncea L.) PADA TANAH ORGANOSOL: APPLICATION OF JAKABA POC FREQUENCY TO GROWTH AND PRODUCTION OF MUSTARD PLANTS (Brassica Juncea L.) ON THE SOIL ORGANOSOL - ibnusina, fedri; Asdiva Sari, Fahyuni (AgriPeat, 2025)
Brassica juncea L. is a green mustard horticultural plant widely consumed by the Indonesian community because it is easy to cultivate, inexpensive, and has high nutritional content. A difficulty that can be faced in the growth of a green mustard production is caused by critical land, such as organosol soil. The use of Eternal Fortune Mushroom (Jakaba) as a Liquid Organic Fertilizer (LOF) by applying a specific frequency of application becomes a potential solution to deal with this issue. This Jakaba POC contains microorganisms that can help improve soil fertility, neutralize soil pH, and enhance physical, chemical, and biological attributes define a of the soil. This study aims to determine the effectiveness of applying Jakaba POC at specific frequency levels on the growth and production of green mustard plants in organosol soil. The methodology utilized in this study involves the Randomized Block Design method with different treatments of 30 ml/l Jakaba POC applied once a week (P1), 15 ml/l Jakaba POC applied twice a week (P2), and 10 ml/l Jakaba POC applied three times a week (P3). The treatment design consisted of 3 levels with 9 replications, resulting in 27 plots or experimental units. The research results show no significant effect between treatments on the observation variables of the amount of foliage, width of leafage, length of leaf blades, height of vegetation, weight of freshly harvested plants, weight of plant cover, root weight, and root length. The application of Jakaba POC once a week is more effective compared to twice a weekly and three times weekly.